Identification and morphological description of the larva of Uloma (Uloma) excisa excisa Gebien, 1914 (Coleoptera: Tenebrionidae: Ulomini) - Liu, Shan-Shan; Ji, Bao-Yue; Liu, Lan-Fang; Ren, Guo-Dong (Zootaxa, 2024)
The larva of Uloma (Uloma) excisa excisa Gebien, 1914, from southern China, is associated with the adult by using molecular phylogenetic analyses based on mtDNA COI sequences. The morphological characteristics of the larva of this species are described and illustrated in detail for the first time. A key to the larvae of three Chinese Uloma species is provided.